1995
DOI: 10.1073/pnas.92.17.7794
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the surfactant protein B gene disrupts surfactant homeostasis, causing respiratory failure in newborn mice.

Abstract: Surfactant protein B (SP-B) is an 8.7-kDa, hydrophobic protein that enhances the spreading and stability of surfactant phospholipids in the alveolus. To further assess the role of SP-B in lung function, the SP-B gene was disrupted by homologous recombination in murine mouse embryonic stem cells. Mice with a single mutated SP-B allele (+/-) were unaffected, whereas homozygous SP-B -/-offspring died of respiratory failure immediately after birth. Lungs of SP-B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
430
4
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 603 publications
(452 citation statements)
references
References 23 publications
16
430
4
2
Order By: Relevance
“…The lack of staining for mature SP-B in lungs from SP-C-TGF-␤1 mice at E18.5 further confirms the inhibitory role of TGF-␤1 on the cytodifferentiation of the alveolar Type II cells. In addition, the lack of mature SP-B may cause neonatal lethality in the TGF-␤1 mice since the targeted disruption of SP-B in mice led to respiratory failure immediately after birth (Clark et al, 1995). Type II cells in TGF-␤1 transgenic mice lacked lamellar bodies, consistent with the absence of SP-B (Clark et al, 1995).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lack of staining for mature SP-B in lungs from SP-C-TGF-␤1 mice at E18.5 further confirms the inhibitory role of TGF-␤1 on the cytodifferentiation of the alveolar Type II cells. In addition, the lack of mature SP-B may cause neonatal lethality in the TGF-␤1 mice since the targeted disruption of SP-B in mice led to respiratory failure immediately after birth (Clark et al, 1995). Type II cells in TGF-␤1 transgenic mice lacked lamellar bodies, consistent with the absence of SP-B (Clark et al, 1995).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the lack of mature SP-B may cause neonatal lethality in the TGF-␤1 mice since the targeted disruption of SP-B in mice led to respiratory failure immediately after birth (Clark et al, 1995). Type II cells in TGF-␤1 transgenic mice lacked lamellar bodies, consistent with the absence of SP-B (Clark et al, 1995). In normal mouse lung, expression of SP-C, SP-B, and CCSP genes are regulated by transcription factors TTF-1 and HNF-3␤.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary surfactant is essential for normal lung function and provides several functions related to local airway conditions, such as enhancement of mucocilliary clearance, improvement of airway stability, encoating, deposition and retention of inhaled substances and particles as well as interaction with infectious agents. We focused our attention on surfactant protein B, because SP-B is necessary for the formation of the active surface film, it is essential for life (Clark et al, 1995) and an association of SP-B variants with acute respiratory failure in COPD was demonstrated (Seifart et al, 2002). Moreover, there is an association of reduced levels of SP-B observed in heterozygous SP-B knockout mice (7/+) with lung physiological abnormalities, decreased lung compliance and increased residual lung volume (Clark et al, 1997), as well as high susceptibility to oxidative lung injury (Tokieda et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Surfactant protein B knock out mice show disruption of surfactant film and function and die from respiratory failure (Clark et al, 1995(Clark et al, , 1997. Furthermore, these mice are more susceptible to oxidative lung injury (Tokieda et al, 1999).…”
mentioning
confidence: 99%
“…Clinical trials have found that artificial surfactants which include SP-B and SP-C are much more efficacious than protein-free surfactant preparations (10). SP-B fulfils a crucial role since hereditary SP-B deficiency is lethal in humans (11) and in SP-B knockout mice (12), while antibodies against SP-B cause RDS in ViVo (13). SP-C deficiency is not lethal at birth (14) but is associated with familial interstitial lung disease (15), and its absence modifies the biophysical properties of monolayers (14).…”
mentioning
confidence: 99%